KARAKTERISTIK SIFAT FISIS DAN MEKANIS LANDFILL SEBAGAI SUBGRADE - Muthia Anggraini; Alfian Saleh; Virgo Trisep Haris (LPPM Universitas Abdurrab, 2022)
The nature of the subgrade plays an important role in road construction. The subgrade can be compacted embankment. The physical and mechanical properties of embankment soil are values ​​or parameters to see the quality requirements. The purpose of this study was to determine the characteristics of the embankment soil as a subgrade. The method used is laboratory testing to obtain the physical and mechanical properties of the embankment soil. Soil samples were taken from Tenayan Raya, Kulim, Pekanbaru City. The results showed that the physical properties of the soil were classified as ML, PI 6.62%, and the mechanical properties of the soil with a CBR value of 17.8%. Conclusion The physical properties of the embankment soil should not contain organic matter and high plasticity. Mechanical properties of embankment soil for CBR value > 10% based on Bina Marga 2018 Revision 2 specifications for selected embankments.